The role of ESG in the REE industry - Ain Nadirah, Romainor; Wan Nada Marhamah, Wan Abdul Razak (The Institution of Engineering and Technology, 2024)
The rare earth element (REE) industry is crucial in developing modern technologies. It plays a significant interest in consumer electronics, electric vehicles as well as military equipment. However, the extraction and processing of the metals often pose environmental effects and social challenges. Thus, this chapter on the REE business looks at how ESG rules affect things. It discusses their effect on protecting nature, dealing with people’s rights, and organising systems in these industries.